Ab initio DFT determination of structural, mechanical, optoelectronic, thermoelectric and thermodynamic properties of RbGeI3 inorganic perovskite for different exchange-correlation functionals. (September 2021) - Deepthi Jayan, K.; Sebastian, Varkey
Abstract: As a potential counterpart to the toxic CH3 NH3 PbI3 for photovoltaic applications, a lead-free non-toxic perovskite, rubidium germanium iodide (RbGeI3 ) is analyzed to assess its structural, mechanical, elastic, optoelectronic, thermoelectric and thermodynamic properties using the Full-Potential Augmented Plane Wave (FP-LAPW) approach of the WIEN2k code using density functional theory. Though various exchange correlation functionals viz. the Perdew Burke Ernzerhof scheme of Generalized Gradient Approximation (PBE-GGA), PBEsol, and WC-GGA are used, the TB-mBJ exchange correlation potential coupled with GGA, provides enhanced results. The lattice constants a0, bulk modulus B and its pressure derivative Bp are estimated to be 11.619096 bohr, 19.34 GPa and 5.4303 respectively with TB-mBJ exchange correlation potential. The elastic constants, C11, C12 and C44, Young's modulus E, Shear modulus G, Poisson's ratio ν and Anisotropic ratio A are estimated to be 43.4 GPa, 7.3 GPa, 7.9 GPa, 27.93 GPa, 11.09 GPa, 0.26 and 0.07 respectively using the Elastic 1.0 package. The density of states (DOS) and band structure are plotted for various exchange correlation functionals. The energy band gap and the absorption coefficient of the material, 1.338 eV and 10 −3 cm −1 respectively, are found to be suitable for photovoltaic applications. Various thermoelectric coefficients like Seebeck coefficient, electrical conductivity and thermal conductivity are also calculated. The thermodynamic properties like Debye temperature, heat capacity, entropy and thermal expansion coefficient are plotted as a function of temperature and pressure using Gibbs2 program. The study indicates that inorganic cubic RbGeI3 has all the characteristics required as an absorber material for perovskite solar cells. However, the phonon dispersion spectrum shows the presence of imaginary modes indicating an instability in the structure with rise in temperature.